SC42 Developing NTS recognition for foundation doctors through joint foundation doctor simulation. (November 2018) - Mason, Timothy
Abstract : Background: Proficient non-technical skills (NTS) within healthcare are widely acknowledged as important for improving patient care. 1 Different specialities have adopted frameworks to aid recognition of these. Simulation education is an effective way to enhance NTS knowledge. 2 Foundation doctors are the most junior doctors in the hospital, often with limited clinical experience. We were keen to explore what knowledge they had of NTS and if this was lacking, to improve it. Summary of project: We incorporated additional features into an existing joint (F1/2) simulation programme. The changes we made included rewriting scenario learning points to emphasise NTS, introducing a simulation NTS observation prompt for those watching (NTS Bingo), introducing distraction exercises for F2s to perform whilst they were waiting for the F1 to escalate to them. Debriefs were heavily NTS focused, and following sessions they were offered work based assessments for reflecting on the scenarios. Regular emails were sent signposting to NTS information, videos and blogs, culminating in creating an NTS infographic which was shared with the foundation doctors. We surveyed the foundation doctors using an online survey tool, before (October 2017) and after (May 2018) the programme to assess knowledge and confidence in NTS. We used a mixture of qualitative questions, Likert scales and yes-no answers. Summary of results: The survey was sent to 83 foundation doctors. There were 33 respondents pre-programme and 35 respondents post programme. Before the programme 36% of junior doctors did not know what NTS consisted of compared to 0% afterwards. 64% said that they had never been formally taught NTS. Post programme 41% of doctors rated themselves as confident or very confident in assessing NTS in themselves or others, compared to 6% pre. 85% said the programme had changed their practice (in relation to NTS) with qualitative answers supporting this. Recognition of NTS 'buzz words' improved after the programme and they rated each intervention we made as helpful in developing their knowledge of NTS Discussion: Whilst other specific teaching interventions through sim have been shown to enhance non-technical skills we were keen to embed this into an already successful programme. The programme was well received from the doctors and these additions will be transferred into other simulation sessions occurring in the hospital. Conclusions/recommendations: Non-technical skill knowledge and recognition can be improved in foundation doctors through targeted additions to a joint foundation doctor simulation programme.